Usability Evaluation of a Dashboard for Home Care Nurses. Issue 1 (January 2019) - Dowding, Dawn; Merrill, Jacqueline A.; Barrón, Yolanda; Onorato, Nicole; Jonas, Karyn; Russell, David
Abstract : The introduction of electronic health records has produced many challenges for clinicians. These include integrating technology into clinical workflow and fragmentation of relevant information across systems. Dashboards, which use visualized data to summarize key patient information, have the potential to address these issues. In this article, we outline a usability evaluation of a dashboard designed for home care nurses. An iterative design process was used, which consisted of (1) contextual inquiry (observation and interviews) with two home care nurses; (2) rapid feedback on paper prototypes of the dashboard (10 nurses); and (3) usability evaluation of the final dashboard prototype (20 nurses). Usability methods and assessments included observation of nurses interacting with the dashboard, the system usability scale, and the Questionnaire for User Interaction Satisfaction short form. The dashboard prototype was deemed to have high usability (mean system usability scale, 73.2 [SD, 18.8]) and was positively evaluated by nurse users. It is important to ensure that technology solutions such as the one proposed in this article are designed with clinical users in mind, to meet their information needs. The design elements of the dashboard outlined in this article could be translated to other electronic health records used in home care settings.